2015
DOI: 10.1586/14737175.2015.1051968
|View full text |Cite
|
Sign up to set email alerts
|

The role of glioma stem cells in chemotherapy resistance and glioblastoma multiforme recurrence

Abstract: Glioma stem cells (GSCs) constitute a slow-dividing, small population within a heterogeneous glioblastoma. They are able to self-renew, recapitulate a whole tumor, and differentiate into other specific GBM subpopulations. Therefore, they have been held responsible for malignant relapse after primary standard therapy and the poor prognosis of recurrent GBM. The failure of current therapies to eliminate specific GSC subpopulations has been considered a major factor contributing to the inevitable recurrence in GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
184
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(202 citation statements)
references
References 107 publications
(145 reference statements)
3
184
0
Order By: Relevance
“…Human BTSC are a slowlydividing, small population within a heterogeneous glioblastoma which can recapitulate a whole tumor and differentiate into other specific GBM subpopulations [51]. Human BTSC tend to preferentially reside within the hypoxic core of tumor mass [52].…”
Section: Discussionmentioning
confidence: 99%
“…Human BTSC are a slowlydividing, small population within a heterogeneous glioblastoma which can recapitulate a whole tumor and differentiate into other specific GBM subpopulations [51]. Human BTSC tend to preferentially reside within the hypoxic core of tumor mass [52].…”
Section: Discussionmentioning
confidence: 99%
“…10,[13][14][15] On the other hand, GBM also appears to have a cellular hierarchy, whereby there exists a subpopulation of GBM cells that are enriched with the capacity for tumor initiation and propagation, and these cells drive tumor growth and treatment resistance. [16][17][18][19] A large number of studies have suggested that WNT signaling is aberrantly activated in GBM and that it promotes GBM growth and invasion via the maintenance of stem cell properties. [20][21][22][23] Here, we will review recent studies from the literature that have described the functions of WNT/β-catenin signaling in development and cancer, with particular emphasis on [24][25][26][27][28][29] genetic and epigenetic alterations that lead to aberrant WNT pathway activation in GBM.…”
mentioning
confidence: 99%
“…Glioblastoma multiforme typically features a high capacity to infi ltrate normal surrounding tissue which is, together with the high radioresistance, the main reason for the poor prognosis for GBM [ 42 ]. Due to the infi ltration a total removal of those TICs is nearly impossible, as physicians can resect the visible tumour but not the cells migrated in adjacent tissues developing metastasis.…”
Section: Glioblastoma Multiforme Treatmentmentioning
confidence: 99%